(untitled) (Journal of the Bangladesh Agricultural University, 2020)
With a view to implementing Precision Agriculture (PA) technologies like Global Positioning System (GPS) and Geographic Information System (GIS) in mechanized harvesting this study was carried out in southern Bangladesh. In this study, the harvesting speed and machine idle time of a mini combine harvester were evaluated from geo-referenced data through visual inspection which was created using a GIS software. The linear speed trendline obtained from the GPS data indicated an average harvesting speed slightly above 2 km/h and GIS mapping showed that the harvester was idle for as long as 15 seconds or more on some occasions. In addition, an attempt was also taken to build a relationship between harvesting speed and heading changes. The results revealed that no significant relationship existed between harvesting speed and heading changes. In the case of machine idle time, from the developed map it could be easily identified where on the field and how much time the machine was idle during the harvesting operation. Application of GPS technology in farm machinery management might create some opportunity to obtain spatial data regarding machine operation. Again, machine data with geo coordinates can enable farmers and farm managers to identify the causes of inadequate machine performance and take actions to increase farm productivity. J Bangladesh Agril Univ 18(3): 751–759, 2020 https://doi.org/10.5455/JBAU.101583